Who owns the pipes? Utility ownership, infrastructure conditions, and methane emissions in United States natural gas distribution. - Scott, Ryan P.; Scott, Tyler A.; Greer, Robert A. (Review of Policy Research, 2022)
Critical infrastructure systems that provide local public services are owned by a complicated array of public and private entities that are subject to disparate regulatory regimes. Determining whether and why performance differences between public and private service providers emerge in these different contexts is critical for understanding the efficacy of current management efforts and informing policy choices about how to deal with public and private service providers. This paper analyzes a census of all U.S. gas distributors and a more detailed sample of the largest utilities in the United States to model how sector and regional market concentration relate to infrastructure quality and leak volumes. Using safety reports, market data, and yearly infrastructure records submitted by gas distributors from 2010 to 2017, the article uses a series of Bayesian hierarchical models to show that publicly owned utilities report lower quality infrastructure (i.e., operation of pipelines with lower quality materials), but also self‐report significantly lower leak rates, all else equal. The article concludes by discussing potential explanations for this discrepancy, including the capital investment incentives private utilities face under cost‐of‐service pricing regulations and the fact that performance measurement capacity is itself a potential outgrowth of increased investment and expenditures.